Investigation of admixed gas effect on plasma nitriding of AISI316L austenitic stainless steel. (November 2021) - Ohtsu, Naofumi; Miura, Koyo; Hirano, Mitsuhiro; Kodama, Kenji
Abstract: The influence of discharge gas composition on the plasma nitriding of AISI316L austenitic stainless steel was investigated using a laboratory-made apparatus consisting of a DC diode and a plasma monitoring system. H2 -N2 and Ar-N2 gas mixtures with various mixture ratios were introduced in the apparatus, and nitriding was performed without auxiliary substrate heating. A >4 μm-thick surface layer, consisting of an expended austenitic phase, γN, was formed on the AISI316L substrate when the optimized H2 -N2 plasma was used. The thickness and maximum nitrogen content of the surface layer increased with an increase in the population of N2 + species in the plasma; the N2 + population in the plasma is considered an underlying parameter for the optimization. Conversely, the penetration of nitrogen into the AISI316L surface was scarce when Ar-N2 plasma was used, irrespective of the gas mixture ratio. Such a phenomenon indicates that Ar-N2 plasma is ineffective for nitriding. However, the effects of H2 -N2 plasma, which are not limited to the surface reaction, are beneficial to facilitate nitriding. Highlights: Nitriding of AISI 316L austeitic stainless steel was analyzed with plasma diagnostics. Thickness and nitrogen content increased with the population of N2 + species in plasma. Formation of nitride layer rarely observed when using Ar-N2 plasma. ~4 μm-thick nitride layer was formed within 10 nin under the optimized H2 -N2 plasma. The effects of H2 -N2 plasma on nitriding are not limited to the surface reaction.